LOW COST TELEMONITORING TECHNOLOGY OF SEMISPHERICAL SOLAR DRYER FOR DRYING ARABICA COFFEE BEANS - Eko Kuncoro PRAMONO; Mirwan Ardiansyah KARIM; Ahmad FUDHOLI; Ramayanty BULAN; Ravipat LAPCHAROENSUK; Agustami SITORUS (My University, 2022)
This study focusses on the development of a low-cost Internet of Things (IoT) system for semispherical solar dryers to dry arabica coffee beans. The temperatures and relative humidity (Rh) of a solar dryer room are measured using a DHT22 sensor module. The moisture content of hard arabica coffee beans is calculated by measuring the mass of the dried product using the load cell sensor module. All detected data are then sent using wireless networks and saved on a database cloud server. Tests are conducted to evaluate the uniformity of the DHT22 sensor module in a semispherical solar dryer, measure the temperature and Rh and reduce the mass of the dried coffee beans. The performance of the DHT22 sensor module at the uniformity testing stage shows promising results in terms of temperature and Rh, with standard deviations of 0.46 and 3.55, respectively. In addition, the performance of the semispherical solar dryer in relation to the drying kinetics of arabica coffee beans is evaluated. Arabica coffee beans are dried from 49.59% (w.b.) to 10% (w.b.) moisture content within 69 h. In addition, the drying kinetics of coffee arabica beans are investigated. Three models are compared with experimental data on arabica coffee beans dried in a semispherical solar dryer. The Page model is selected to represent the thin layer drying behaviour of arabica coffee beans.
Keywords: Arabica coffee; Food Drying and Modeling